Legal Analysis of the Nature of Cyber Currency in Iran: A Comparison to EU Law - Nima Norouzi (Indonesian Journal of Law and Society, 2021)
Electronic money as the monetary value stored in an electronic instrument is the last step in the gradual evolution of money, described as the immaterialization and invisibility of money. It is an emerging phenomenon that can perform the functions and duties of money. This study aimed to investigate the legal concept of cyber currency in Iran-Islamic and EU law in a comparative view. This study mainly considered e-money as a payment method and discusses it from different perspectives. In analyzing the legal nature of this phenomenon, it used two different approaches by combining an empirical-analytical method and a comparative study. The first approach was to analyze the nature of electronic money as a type of money. The second was to analyze the nature of electronic money in the light of non-monetary theories and describe it as one of the legal institutions used in business. This study concluded that electronic money would have different legal effects in its legal analysis, depending on who the publisher and acceptor are and how its publication and circulation process is defined and explained. The description of electronic money in the form of non-monetary theories ignored its role as an efficient payment tool in today's advanced business environment. KEYWORDS: Electronic Money, Cyber Currency, Islamic Law.